Uncertainty in healthcare and health decision making: Five methodological and conceptual research recommendations from an interdisciplinary team. - Simonovic, Nicolle; Taber, Jennifer M.; Scherr, Courtney L.; Dean, Marleah; Hua, Jacqueline; Howell, Jennifer L.; Chaudhry, Beenish M.; Wain, Karen E.; Politi, Mary C. (Journal of Behavioral Medicine, 2023)
Uncertainty is prevalent in various health contexts. It is imperative to understand how health-related uncertainty can impact individuals' healthcare experiences and health decision making. The purpose of the present paper is to provide five overarching recommendations from an interdisciplinary team of experts to address gaps in the literature on health-related uncertainty. We present a case study of health-related uncertainty within the specific context of alcohol use to demonstrate these gaps and provide context for the recommendations. The five recommendations concerning health-related uncertainty include: (1) use common, consistent terminology to discuss uncertainty, (2) clarify measures of individual differences in response to uncertainty, (3) increase research on uncertainty and affect, (4) investigate the impact of the channel through which uncertainty is communicated, and (5) develop theory-driven interventions to improve uncertainty management. We conclude by reviewing health contexts in which health-related uncertainty exists and note how our recommendations complement existing reviews and data.